DAYA TARIK KOPI ARABIKA DARI PERSPEKTIF PERILAKU KONSUMEN - Fernandez, F.X Edy; Septiadi, Dudi (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
Arabica coffee is known to have superior quality and taste compared to other types of coffee, making it the main choice for many coffee lovers. This research aims to examine the attractiveness of Arabica coffee from the perspective of consumer behavior in Mataram City. This research uses a descriptive method with a quantitative approach. Data was collected through a survey with a questionnaire distributed to 30 respondents who were coffee consumers in Mataram City. The research results show that consumer behavior in purchasing Arabica coffee in Mataram City, at the introduction stage, consumers choose Arabica coffee because they like it and are used to consuming it. They look for information that is influenced by themselves, friends, family, and social media. The calculation results show that the attribute most considered by Arabica coffee consumers in Mataram City is the aroma of the coffee. In situations where the desired Arabica coffee is not available, consumers tend to choose other types of coffee that are available at the same place. The quality of the taste and aroma of Arabica coffee is the most dominant factor influencing purchasing decisions, followed by competitive prices and a strong brand image. Apart from that, this research also found that consumer preferences for Arabica coffee are influenced by lifestyle trends and awareness of the health benefits of coffee